Implementasi Sistem Monitoring Suhu dan Kualitas Udara Berbasis Internet of Things (IoT) dengan Kontrol Blower Otomatis - Indra Gunawan; Muhamad Sadali; M. Nurul Wathoni; M. Taupik Hidayat Ramdan (Fakultas Teknik Universitas Hamzanwadi, 2026)
Monitoring temperature and air quality are important factors in creating a comfortable and safe treatment room environment for patients. This study aims to design and implement an Internet of Things (IoT)-based temperature and air quality monitoring system integrated with automatic blower control. The system was developed using the Research and Development (R&D) method by utilizing a DHT22 sensor for temperature and humidity measurement and an MQ135 sensor for air quality detection, controlled by NodeMCU ESP8266. The system was tested by comparing the temperature sensor readings with a thermohygrometer and testing the system's response to changes in environmental conditions. The test results showed that the system was able to monitor temperature and air quality in real-time with a temperature measurement error rate of 0.21% and was able to activate the blower automatically when the temperature and air quality values exceeded the specified thresholds. Thus, the developed system proved to work well and can be used as an IoT-based environmental monitoring solution for treatment rooms.